Cross-border transmission of climate policies through global production networks - Marius Fourné (Halle Institute for Economic Research (IWH), 2025)
Climate policies do not operate in isolation but propagate through global production networks, affecting industries beyond national borders. This paper combines international input-output data with a granular instrumental variable approach to capture how foreign regulations transmit through upstream and downstream linkages. Distinguishing between market-based policies, non-market regulations, and technology support, the analysis shows that foreign climate policies can enhance domestic productivity, with effects shaped by industry characteristics and operating through technological adjustment along supply chains. The results underscore the importance of accounting for international spillovers when evaluating the economic impact of environmental regulation.
Keywords: F18; L16; O44; Q37; 330; climate policy; environmental regulations; global value chains; green innovation; international trade; productivity